2023
DOI: 10.1186/s12893-023-01961-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic mesh versus biological mesh to prevent incisional hernia after loop-ileostomy closure: a randomized feasibility trial

Abstract: Background Incisional hernia is a frequent complication after loop-ileostomy closure, rationalizing hernia prevention. Biological meshes have been widely used in contaminated surgical sites instead of synthetic meshes in fear of mesh related complications. However, previous studies on meshes does not support this practice. The aim of Preloop trial was to study the safety and efficacy of synthetic mesh compared to a biological mesh in incisional hernia prevention after loop-ileostomy closure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Despite concerns with synthetic mesh, Rosen et al 11 have successfully demonstrated that it can be considered in contaminated VHR when placed in the retromuscular position with superior outcomes to biologic mesh. Other studies reflect this shift toward using synthetic mesh in certain contaminated environments 29,32–34 . Our results demonstrate that the use of biosynthetic mesh shows similar outcomes to synthetic mesh, making P4HB a viable option for surgeons due to its relatively low infection rates and sustained QoL improvement.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Despite concerns with synthetic mesh, Rosen et al 11 have successfully demonstrated that it can be considered in contaminated VHR when placed in the retromuscular position with superior outcomes to biologic mesh. Other studies reflect this shift toward using synthetic mesh in certain contaminated environments 29,32–34 . Our results demonstrate that the use of biosynthetic mesh shows similar outcomes to synthetic mesh, making P4HB a viable option for surgeons due to its relatively low infection rates and sustained QoL improvement.…”
Section: Discussionsupporting
confidence: 58%
“…Other studies reflect this shift toward using synthetic mesh in certain contaminated environments. 29,[32][33][34] Our results demonstrate that the use of biosynthetic mesh shows similar outcomes to synthetic mesh, making P4HB a viable option for surgeons due to its relatively low infection rates and sustained QoL improvement.…”
Section: Discussionmentioning
confidence: 62%
“…, low rates of incisional hernia and no surgical site infection)[ 12 , 15 ]. Results have compared favorably to synthetic mesh repairs[ 16 ] and direct tissue repair[ 17 ]. A large randomized controlled trial of 790 patients undergoing elective ileostomy or colostomy closure were assigned to receive suture alone or biologic mesh augmented stoma takedown.…”
Section: Introductionmentioning
confidence: 99%